U C Berkeley Heavy Reunion at Holiday Inn San Francisco - Watkins, Howard::::::::: (1981)
Kirk Wilson, Christine Watkins, David Morse, Howard Watkins, David Atkinson, Joe Barkett, Frank Gumpert, and Jerry Neary